Patterns of diabetic patients visit in emergency department in tertiary care hospital - Bajracharya, Manjita; Batajoo, Kabita Hada; Shrestha, Trishna; Pradhananga, Sneha (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction: Diabetes mellitus is a global health problem with increasing incidence worldwide in an epidemic  form including Nepal. This chronic disease leads to many complications, hospital admissions and premature morbidity and mortality. This study aimed to study the cause and number of emergency visits and to evaluate the rate and duration of hospitalisation among diabetic patients who visit the emergency departmentMethod: This was an observational cross-sectional study including 98 diabetic patients of >18 years presenting to emergency department of KIST medical college and teaching hospital between January 2020 to June 2020. The number and reason of emergency visits as well as number and duration of hospitalization was recorded in a semi structured proforma. The data entry was done in Microsoft Excel and analysis was done using the SPSS 24.Result: While 61 cases (62.2%) of this sample utilized the emergency department (ED) services in last 12 months’ period, 32.7% reported using ED once and 23.5% used 2-3 times and only 6% of the subjects had visited emergency more than 4 times within 12 months. Heart disease (18.1%) and infections (18.1%) were the most common reason for ED visit. There were 62 (63.3%) admissions from ED, 32.2% patients were hospitalized for 1-3 days, 50% were hospitalized for 3-7 days and 17.8% stayed for 1-2 weeks’ duration in the hospital.Conclusion: Majority of the diabetic patients had utilized ED more than once in past 12 months and the most common cause was found to be related to cardiac illness and infections. More than half of the diabetic patients visiting ED were admitted for mostly 3-7 days’ duration.